Factors influencing resident’s decision to reside in gated and guarded - Shamsudin, Zarina; Zainal, Rozlin; Seow, Ta Wee; Mat Radzuan, Indera Syahrul; Sulaiman, Noralfishah; Mohd Diah, Mohd Lizam; Shamsudin, Shafiza (School of Engineering, Taylor’s University, 2017)
Gated communities are residential areas developed with restricted access with strictly controlled entrances and surrounded by a close perimeter of wall or fences. Developers, conscious of the need to fulfil the requirement of living in modern and sophisticated lifestyle and gated properties become the trend and mushroomed over the past decade. Nowadays, it is obvious that gated and guarded communities become almost a dominant feature of Malaysia housing development projects. The focus of this paper is to identify the factors contribute resident’s decision to reside in gated and guarded community and to study social interaction among gated communities’ residents. 150 questionnaires were distributed to the residents of selected gated and guarded community area in order to achieve the objectives and analysed by using Statistical Package for Social Science (SPSS) and descriptive analysis. The result was tabulated and presented in charts and graphs for a clear and better understanding. The five main factors contribute to resident decision to reside in gated communities were identified and ranked; there are privacy, security, location, lifestyle and prestige. Besides, the residents are feeling neutral towards the facilities and services provided in their gated and guarded residential area. A comprehensive improvement towards the facilities and services is needed to reach higher satisfaction from the residents.